(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID 19 pandemic has caused widespread disruption by adversely impacting global businesses and economies and posed a challenge to business sustainability by exposing business entities to new risks and opportunities. The present study has been undertaken to analyze the impact of COVID 19 pandemic on corporate sustainability with reference to selected UAE companies and how organizations could cope up with the crisis to achieve sustainable development. It has been identified that corporate social responsibility is a business model that helps any organization to be socially accountable in relation to the public, stakeholders, and the organization itself. Descriptive research design was selected as the objective of the study is to investigate the impact of COVID 19 on CSR and sustainability. Ten different companies in UAE were selected and random sampling was used to select the companies for this study as the population of this research was confined to companies in UAE regardless of their nature, size, and level. From the overall analysis it can be concluded that corporate social responsibility and sustainability play vital roles in the business organizations in UAE. According to the results, the pandemic has positive impacts on CSR since many companies are willing to work at the social level. It is important for companies to have social auditing, a code of conduct, self-regulation, and accountability to ensure socially responsible actions. Companies which incorporated sustainability into their company operations prior to the pandemic were more flexible in responding to unanticipated events.